Determination of the lime requirement of sandy, organic-rich, and structured, high Mg:Ca ratio soils by the Eksteen method - Smuts, Michiel Nicolaas (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2001.